(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Rupi Kaur is an Indian Canadian poetess raising voice for the multiple tabooed female oriented themes and subjects. Her point of views in instapoetry has raised many thought-provoking instances yet controversial debates too; she began her instapoetry career with Milk and Honey; followed by two more books The Sun and Her Flowers and Homebody. The fascinating part is this that she gives drawing illustrations with her writing pieces too. As far this study is concerned, it is an attempt to explore body image in terms of how the poetess portrays body image of contemporary females in her work. To start with, body image is aligned with power struggles and patriarchal dynamics in many cultures and eras. To Bartky, it sounds really controlled in many variant forms and manifestations. She points out how patriarchal domination is modernized which is visible in the works of Foucault.